KERAGAMAN KEMAMPUAN MATEMATIS DENGAN IMPLEMENTASI PENDEKATAN TARL PESERTA DIDIK KELAS VI-D SD DJAMA???ATUL ICHWAN SURAKARTA - Desma Candrasari (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The learning approach used does not accommodate the diversity of each student's initial mathematical abilities, so the learning process becomes less efficient. Teachers need to use the TaRL approach to accommodate the diversity of students' initial mathematical abilities. The subjects used were 27 students from class VI-D of SD Djama'atul Ichwan Surakarta with a variety of initial mathematical abilities. Data collection techniques use observation, interview and documentation techniques. Data triangulation technique for analyzing data obtained through the process of data reduction, presentation and drawing conclusions. Based on the results of the study, the application of differentiated learning through the Teaching at the Right Level (TaRL) approach to the mathematical abilities of class VI-D students at SD Djama'atul Ichwan Surakarta makes the learning process more meaningful because it is in accordance with the mathematical abilities of each student. This is because differentiated learning with the TaRL approach makes it easier for students to participate during the learning process.